2010
DOI: 10.1111/j.1467-9221.2010.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure and Dynamics of Human Thought: The Legacy of William J. McGuire for Social and Political Psychology

Abstract: We humans seem to have evolved with a need to know, a need to represent reality to ourselves insofar as our cognitive apparatus allows. This representational or knowing process appears to be a crucial aspect of our mode of coping with the environment. It is the tragedy of knowledge that this process, which we cannot do without, we cannot do well: it inevitably misrepresents the environment both by oversimplifying and by distorting it. . . . The only thing more outrageous than using our faulty intellectual proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 127 publications
1
7
0
Order By: Relevance
“…Furthermore, each of these threats could precipitate remote ramifi cations or ripple effects that infl uence the individual's degree of attachment to both local and global social systems (cf. Jost & Hardin, 2011). On a meta-theoretical level, the present set of fi ndings are in line with observations that seemingly disparate outcomes and processes can serve the same underlying psychological needs (e.g., see Arndt et al, 2002;Heine et al, 2006;Kay et al, 2008;Solomon et al, 2004;Tesser, 2000).…”
Section: American System Justificationsupporting
confidence: 67%
“…Furthermore, each of these threats could precipitate remote ramifi cations or ripple effects that infl uence the individual's degree of attachment to both local and global social systems (cf. Jost & Hardin, 2011). On a meta-theoretical level, the present set of fi ndings are in line with observations that seemingly disparate outcomes and processes can serve the same underlying psychological needs (e.g., see Arndt et al, 2002;Heine et al, 2006;Kay et al, 2008;Solomon et al, 2004;Tesser, 2000).…”
Section: American System Justificationsupporting
confidence: 67%
“…One of the most trenchant social and political psychologists of the twentieth century, William J. McGuire (), observed that the “politics and psychology relationship has been lively and long‐lasting as interdisciplinary affairs go, its longevity fostered by frequent shiftings of its popular topics, methods, and theories” (p. 363; see also Jost & Hardin, ). As in all sustainable relationships, psychology and political science have, for the most part, changed together rather than grown apart (e.g., see Huddy, Sears, & Levy, ; McGuire, ; Sears, Huddy, & Jervis, ).…”
mentioning
confidence: 99%
“…long-lasting as interdisciplinary affairs go, its longevity fostered by frequent shiftings of its popular topics, methods, and theories" (p. 363; see also Jost & Hardin, 2011). As in all sustainable relationships, psychology and political science have, for the most part, changed together rather than grown apart (e.g., see Huddy, Sears, & Levy, 2013;McGuire, 1993;Sears, Huddy, & Jervis, 2003).…”
mentioning
confidence: 99%
“…Although McGuire is best known for his empirical research on persuasion and social influence, he contributed profoundly to numerous areas of scholarship and research, including creative theorizing about society, culture, and evolution, which is the subject of the essay published here. Additional biographical and autobiographical information about William J. McGuire may be found in the following sources: Banaji and Hastie (), Evans (), Hunyady and Jost (), Jost and Banaji (), Jost, Banaji, and Prentice (), Jost and Hardin (), McGuire (), Pearce ().…”
Section: A Previously Unpublished Manuscript (Edited With An Introducmentioning
confidence: 99%